Religious Understanding of Central Java Communities through the AISAS Digital Literacy model in accessing Religious Content - Siti Maemunah; Ahmad Rouf; Gita Maulida Nanda Utami (Kopertais Wilayah X Jawa Tengah, 2026)
Community religious understanding can not only be obtained from sources or people who are religious experts/clerics, along with technological developments, people often use online media as a reference for information that can lead opinions and mindsets about religious understanding. This study was conducted on 600 respondents spread across several areas of Central Java to determine the level of community religious understanding and online behavior through digital literacy which can give rise to different perceptions in understanding religious content and even cause intolerant behavior in society. This study was conducted using a survey method and analyzed qualitatively in order to present a real picture of what is happening in society. The results of the study found that there are still many people who have low AISAS literacy patterns so that they are easily influenced by online media content and can lead to intolerant understanding due to differences in religious understanding. Community religious understanding has been seen well with the internalization of religious values ​​that are upheld and combined with the culture of the surrounding community. However, the influence of inappropriate digital literacy can actually provide negative perceptions that can cause disputes in society.